Axial Skeletal Location Predicts Poor Outcome in Ewing's Sarcoma: A Single Institution Experience. (24th November 2011) - Weiss, Kurt R.; Biau, David J.; Bhumbra, Rej; Griffin, Anthony M.; Blackstein, Martin E.; Chung, Peter; Catton, Charles; O'Sullivan, Brian; Ferguson, Peter C.; Wunder, Jay S.
Abstract : Introduction . Ewing's sarcomas (EWSs) of bone and soft tissue are neuroectodermal tumors that affect both axial and appendicular locations. We hypothesized that axial location predicted poor outcome in EWS patients. Materials and Methods . Sixty-seven patients (57 with bone EWS and 10 with soft tissue EWS) were identified from our database. Thirty-four (51%) had axial EWS and 33 (49%) had appendicular EWS. Statistical analyses identified predictors of poor outcome. Results and Discussion . Axial location, large size, metastases at presentation, lack of definitive treatment, and positive surgical margins all correlated with poor outcome in univariate analysis. In multivariate analysis, axial location still predicted poor outcome when adjusted for pretreatment variables. Axial location was not statistically predictive of poor outcome when adjusted for treatment variables. Conclusions . Anatomic location has a negative effect on outcome in EWS that cannot be completely explained by pretreatment or treatment factors. Additional studies are required to determine if there is a biologic difference between axial and appendicular EWS.